A Versatile Field Instrument for Foresters, Surveyors, Engineers and Plane-tablers - Kadambi, K. (Indian Forester, 1950)
A short history of camphor, its demand and supply, its need by India and non-availability of any Indian raw material for its production is given. Experimental cultivation of a quick-growing and early camphor-yielding plant (Ocimum kilimandscharicum, Guerke.) at the Forest Research Institute, Dehra Dun, is described. Climatic and edaphic requirements of the new plant, methods of propagation and extraction of camphor are briefly described.